Self-gender schemes: A comparison between individual and collective sport modalities - Cardoso, F.L.; Pinheiro Ferrari, E.; Da Silva, W.R.; Medeiros, T.E.; Melo, G. (Cuadernos de Psicología del Deporte, 2017)
e aim of this study was to analyze the dierences in gender schemas of self between collective and individual sports. e participants were 140 amateur athletes aged between 13 and 17 years practicing a team sport (indoor soccer) and an individual sport (athletics) in the Chapecó and Florianópolis municipalities of Santa Catarina-SC. e instruments used were the Questionnaire for Socio-Demographic and Training, the Inven- tory Female Gender Schemas of Self-Concept (IFEGA) and the Inventory of Male Gender Schemas of Self-Concept (IMEGA). No dierences in gender schema were found among women athletes who were mostly classi- ed as masculine/ feminine (iso schematic). Among men, the soccer players showed a hetero masculine gender schema, while those in athletics showed an iso schematic scheme. Regarding the variation within the gender schema dimensions, the soccer athletes had higher values in terms of inferiority in relation to those in athletics. Among men, the athletics athletes showed higher values of boldness and lower values of insecurity as compared to soccer athletes. We conclude that gender schemas of self-concept only had variations in the two modalities for male athletes; however, the variations in their constitutive dimensions of schema occurred according to the nature of the sport practiced.